Sensorimotor Alpha Activity is Modulated in Response to the Observation of Pain in Others - Whitmarsh, Stephen; Nieuwenhuis, Ingrid L.; Barendregt, Henk; Jensen, Ole (Frontiers in Human Neuroscience, 2011)
The perception-action account of empathy states that observation of another person's state automatically activates a similar state in the observer. It is still unclear in what way ongoing sensorimotor alpha oscillations are involved in this process. Although they have been repeatedly been implicated in (biological) action observation and understanding communicative gestures, less is known about their role in vicarious pain observation. Their role is understood as providing a graded inhibition through functional inhibition, thereby streamlining information flow through the cortex. Although alpha oscillations have been shown to have at least visual and sensorimotor origins, only the latter are expected to be involved in the empathetic response. Here, we used magnetoencephalography (MEG), allowing us to spatially distinguish and localize oscillatory components using beamformer source reconstruction. Subjects observed realistic pictures of limbs in painful and no-pain (control) conditions. As predicted, time-frequency analysis indeed showed increased alpha suppression in the pain condition compared to the no-pain (control) condition. Although both pain and non-pain conditions suppressed alpha and beta band activity at both posterior and central sensors, the pain condition suppressed alpha more only at central sensors. Source reconstruction localized these differences along the central sulcus. Our results could not be accounted by differences in the evoked fields, suggesting a unique role of oscillatory activity in empathetic responses. We argue that alpha oscillations provide a unique measure of the underlying functional architecture of the brain, suggesting an automatic disinhibition of the sensorimotor cortices in response to the observation of pain in others.